ABC of prehospital emergency medicine - Nutbeam, Tim; Boylan, Matthew (ABC series (Malden, Mass.), 2013)
"This brand new title in the ABC series provides a comprehensive overview of pre-hospital medicine, including transport, patient assessment, emergency care systems, and pre-hospital interventions. With pre-hospital care being the start of the 'trauma chain', the treatment patients receive on-scene as well as en-route can be life-saving, and this new title is invaluabe for all staff involved in emergency and pre-hospital medicine"--Provided by publisher.